Про “батьківство” та “материнство” на Лівобережній Україні другої половини ХVІІІ ст. - Маслійчук, В. (Народна творчість та етнографія, 2008)
The paper deals with parental love in time of social transformation. Ukrainian folklore accented the respect to parents and obedience of children. Archival examples affirmed the disrespect of children and fighting between child and parents. In the Left-Bank Ukraine parental care was more than just taking care of parents.